Ring Extensions with Finitely Many Non-Artinian Intermediate Rings. (12th November 2020) - Jarboui, Noômen; Al-Kuleab, Naseam; Almallah, Omar
Abstract : The commutative ring extensions with exactly two non-Artinian intermediate rings are characterized. An initial step involves the description of the commutative ring extensions with only one non-Artinian intermediate ring.